Novel Field-Programmable Gate Array Architecture for Computing the Eigenvalue Decomposition of Para-Hermitian Polynomial Matrices - Kasap, Server; Redif, Soydan (IEEE Trans. on Very Large Scale Integration (VLSI) Systems)

Competitive throughput in multi-hop wireless networks despite adaptive jamming - W. Richa, Andréa; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Distributed Computing)

Corona: A stabilizing deterministic message-passing skip list - Mohd Nor, Rizal; Nesterenko, Mikhail; Scheideler, Christian (Theor. Comput. Sci.)

An Efficient and Fair MAC Protocol Robust to Reactive Interference - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (IEEE/ACM Trans. Netw.)

Quelltextgenerierung für LEGO Mindstorms-Roboter - Geismann, Johannes (Berichtsband der Informatiktage 2013: Smarte Sichten, smarte Schichten)
Die Komplexität von mechatronischen Systemen wird stetig größer. MechatronicUML (MUML) ist eine Methode zur Entwicklung für Software von mechatronischen Systemen. Im Rahmen einer Bachelorarbeit wurde ein bestehender Quelltextgenerator für MUML-Modelle so erweitert, dass Quelltext für ein Echtzeitbetriebssystem generiert werden kann, welches auf einem LEGO Mindstorms-Roboter installiert ist.

Modulare Leistungsprognose von Kompaktsteuerungen - Frieben, Jens; Heutger, Henning; Meyer, Matthias; Becker, Steffen (9. Paderborner Workshop Entwurf mechatronischer Systeme)

An evaluation testbed for adaptive, topology-aware deployment of elastic applications - Keller, Matthias; Robbert, Christoph; Peuster, Manuel (Proceedings of the ACM SIGCOMM 2013 conference on SIGCOMM)

CROWD: An SDN Approach for DenseNets - Ali-Ahmad, Hassan; Cicconetti, Claudio; de la Oliva, Antonio; Draxler, Martin; Gupta, Rohit; Mancuso, Vincenzo; Roullet, Laurent; Sciancalepore, Vincenzo (2013 Second European Workshop on Software Defined Networks)

A Scalable Redundant TDMA Protocol for High-Density WSNs Inside an Aircraft - Blanckenstein, Johannes; Garcia-Jimenez, Javier; Klaue, Jirka; Karl, Holger (Lecture Notes in Electrical Engineering)

Cliquenbildung in verteilten Systemen - Blumentritt, Fritz

Adding Capacity-Aware Storage Indirection to Homogeneous Distributed Hash Tables - Wette, P.; Graffi, K. (2013 Conference on Networked Systems)

OpenNetInf - prototyping an information-centric Network Architecture - Dannewitz, Christian; Herlich, Matthias; Karl, Holger (37th Annual IEEE Conference on Local Computer Networks -- Workshops)

Denser Networks for the Future Internet, the CROWD Approach - de la Oliva, Antonio; Morelli, Arianna; Mancuso, Vincenzo; Draexler, Martin; Hentschel, Tim; Melia, Telemaco; Seite, Pierrick; Cicconetti, Claudio (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering)

Intelligenz in der Produktion - Spitzencluster it's OWL als Wegbereiter für Industrie 4.0 - Dumitrescu, Roman; Kühn, Arno (Markt&Technik Summit Industrie 4.0, München, 16. - 17. Okt. 2013)

Von der Anforderungserfassung bis zur Funktionsstruktur - Ein Systems Engineering-Vorgehen für die industrielle Praxis - Schmitt, Nicolas; Kaiser, Lydia; Dumitrescu, Roman; Hofmann, Maik (Tag des Systems Engineering)

Hybrid-Actuated Finger Prosthesis with Tactile Sensing - Low, Cheng Yee; Kasim, Mohamad Amlie Abu; Koch, Torben; Dumitrescu, Roman; Yussof, Hanafiah; Jaafar, Roseleena; Jaafar, Ahmed; Aqilah, Ahsana; Ng, Kok Mun (International Journal of Advanced Robotic Systems)

Strategy Planning of Collaborative Humanoid Soccer Robots based on Principle Solution - Low, Cheng; Aldemir, Mustafa; Aziz, Norheliena; Dumitrescu, Roman; Anacker, Harald (Journal of Production Engineering Research & Development (PERE) 7)

The Need to Start Research Education Early - Joel, W. J. (IEEE Computer Graphics and Applications)

Information Visualization Courses for Students with a Computer Science Background - Kerren, A. (IEEE Computer Graphics and Applications)

Building Virtual Worlds Carrying on the Legacy of Randy Pausch's "Head Fake" - Schell, J.; Klug, C. (IEEE Computer Graphics and Applications)

A Variational Approach to Modeling Slow Processes in Stochastic Dynamical Systems - Noé, Frank; Nüske, Feliks (Multiscale Modeling & Simulation)

Network of Information (NetInf) - An information-centric networking architecture - Dannewitz, Christian; Kutscher, Dirk; Ohlman, B; Farrell, Stephen; Ahlgren, Bengt; Karl, Holger (Computer Communications)

Improving Cooperative Transmission Feasibility by Network Reconfiguration in Limited Backhaul Networks - Dräxler, Martin; Biermann, Thorsten; Karl, Holger (International Journal of Wireless Information Networks)

Trade-off between latency and coverage in cooperative radio access networks - Hohenberger, Till; Herlich, Matthias; Karl, Holger (IEEE International Conference on Advanced Networks and Telecommunications Systems, ANTS 2013, Kattankulathur, India, December 15-18, 2013)

NetIDE: First Steps towards an Integrated Development Environment for Portable Network Apps - M. Facca, Federico; Salvadori, Elio; Karl, Holger; R. Lopez, Diego; Arranda Gutierrez, Pedro; Kostic, Dejan; Riggio, Roberto (Second European Workshop on Software Defined Networks, EWSDN 2013, Berlin, Germany, October 10-11, 2013)

The playground of Wireless Dense networks of the future - Cicconetti, Claudio; Morelli, Arianna; Dräxler, Martin; Karl, Holger; Mancuso, Vincenzo; Sciancalepore, Vincenzo; Gupta, Rohit; de la Oliva, Antonio; Isabel Sanchez, M.; Serrano, Pablo; Roullet, Laurent (2013 Future Network & Mobile Summit, Lisboa, Portugal, July 3-5, 2013)

A topology-aware adaptive deployment framework for elastic applications - Keller, Matthias; Peuster, Manuel; Robbert, Christoph; Karl, Holger (17th International Conference on Intelligence in Next Generation Networks, ICIN 2013, Venice, Italy, October 15-16, 2013)

Energy-Efficient Assignment of User Equipment to Cooperative Base Stations - Herlich, Matthias; Karl, Holger (ISWCS 2013, The Tenth International Symposium on Wireless Communication Systems, Ilmenau, Germany, August 27-30, 2013)

Vorgehensmodelle 2013: Vorgehensmodelle - Anspruch und Wirklichkeit - Proceedings der 20. Tagung der Fachgruppe Vorgehensmodelle im Fachgebiet Wirtschaftsinformatik (WI-VM) der Gesellschaft für Informatik e.V., Lörrach (Germany)

Cross-layer scheduling for multi-quality video streaming in cellular wireless networks - Dräxler, Martin; Karl, Holger (2013 9th International Wireless Communications and Mobile Computing Conference, IWCMC 2013, Sardinia, Italy, July 1-5, 2013)

Anticipatory Buffer Control and Quality Selection for Wireless Video Streaming - Dräxler, Martin; Blobel, Johannes; Dreimann, Philipp; Valentin, Stefan; Karl, Holger (CoRR)

Ensuring Consistency Among Business Goals and Business Process Models - Nagel, Benjamin; Gerth, Christian; Post, Jennifer; Engels, Gregor (Proceedings of the 17th IEEE International EDOC Conference (EDOC'13))
The paradigm of service-oriented architectures has emerged as an architectural style for designing enterprise applications. Requirements engineering for such applications comprises the specification of business goal models representing stakeholder objectives and the operationalization to business process models that specify the required composition of services. Inconsistencies between business goals and derived business processes can lead to service compositions that are not in line with the actual stakeholder objectives. For preserving consistency it is required to consider logical and temporal dependencies among goals (e.g. the order in which they need to be achieved) in the derivation of business processes. In previous work, we provided a technique for the elicitation and specification of dependencies between business goals. Extending this approach, we aim at validating the consistency between business goal models and business process models regarding these dependencies. In this paper, we present a pattern-based approach for the automated generation of verifiable business process quality constraints from business goal models. We describe how these constraints can be used to check the consistency between business goals and business processes and demonstrate the applicability of our approach in a case study by using the implemented tool support.

Modellbasierte Bewertung von Testprozessen nach TPI NEXT® mit Geschäftsprozess-Mustern - Schumacher, Claudia; Engels, Gregor; Güldali, Baris; Niehammer, Markus; Hamburg, Matthias (Proceedings of the conference on Software Enginneering, Fachtagung des GI Fachbereichs Softwaretechnik (SE 2013), Aachen (Germany))

On-the-Fly Computing - Das Entwicklungs- und Betriebsparadigma für Softwaresysteme der Zukunft - Engels, Gregor (Software Engineering 2013)

Automated Service Composition for On-the-Fly SOAs - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the 11th International Conference on Service Oriented Computing (ICSOC'13))

High-Quality Specification of Self-Adaptive Software Systems - Luckey, Markus; Engels, Gregor (Proceeding of the 8th international symposium on Software engineering for adaptive and self-managing systems)

Decision Support via Automated Metric Comparison for the Palladio-based Performance Blame Analysis - Brüseke, Frank; Becker, Steffen; Engels, Gregor (Proceedings of the 4th ACM/SPEC International Conference on Performance Engineering (ICPE 2013), Prague (Czech Republic))

Performance Analysis of Self-Adaptive Systems for Requirements Validation at Design-Time - Becker, Matthias; Luckey, Markus; Becker, Steffen (Ninth International ACM Sigsoft Conference on the Quality of Software Architectures)

Integrating Coverage Analysis into Test-driven Development of Model Transformations - Küster, Jochen; Kovács, Dániel; Bauer, Eduard; Gerth, Christian

Automated Service Discovery and Composition for On-the-Fly SOAs - Huma, Zille; Gerth, Christian; Engels, Gregor

Konzeption modellbasierter Benutzungsschnittstellen für verteilte Selbstbedienungssysteme - Yigitbas, Enes; Gerth, Christian; Sauer, Stefan (Informatik 2013, 43. Jahrestagung der Gesellschaft für Informatik e.V. (GI), Informatik angepasst an Mensch, Organisation und Umwelt, 16.-20. September 2013, Koblenz, Deutschland)

A Taxonomy-Based Approach towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard (Distributed, Ambient, and Pervasive Interactions)

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten (Design, User Experience, and Usability. Design Philosophy, Methods, and Tools)

Do You Speak Usability? - Aktueller Stand des Glossars und des Curriculums für den Certified Professional for Usability and User Experience (CPUX) der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter (Jahresband Usability Professionals)

Zero Overhead Runtime Monitoring - Wonisch, Daniel; Schremmer, Alexander; Wehrheim, Heike (Proceedings of the 11th International Conference on Software Engineering and Formal Methods (SEFM))
Runtime monitoring aims at ensuring program safety by monitoring the program's behaviour during execution and taking appropriate action before a program violates some property.Runtime monitoring is in particular important when an exhaustive formal verification fails. While the approach allows for a safe execution of programs, it may impose a significant runtime overhead.In this paper, we propose a novel technique combining verification and monitoring which incurs no overhead during runtime at all. The technique proceeds by using the inconclusive result of a verification run as the basis for transforming the program into one where all potential points of failure are replaced by HALT statements. The new program is safe by construction, behaviourally equivalent to the original program (except for unsafe behaviour),and has the same performance characteristics.

Which Flows Are Hiding Behind My Wildcard Rule? Adding Packet Sampling to OpenFlow - Wette, Philip; Karl, Holger (Proceedings of the ACM SIGCOMM '13)
In OpenFlow [1], multiple switches share the same control plane which is centralized atwhat is called the OpenFlow controller. A switch only consists of a forwarding plane. Rules for forwarding individual packets (called ow entries in OpenFlow) are pushed from the controller to the switches. In a network with a high arrival rate of new ows, such as in a data center, the control trac between the switch and controller can become very high. As a consequence, routing of new ows will be slow. One way to reduce control trac is to use wildcarded ow entries. Wildcard ow entries can be used to create default routes in the network. However, since switches do not keep track of ows covered by a wildcard ow entry, the controller no longer has knowledge about individual ows. To nd out about these individual ows we propose an extension to the current OpenFlow standard to enable packet sampling of wildcard ow entries.

Verteilte Erstellung und Aktualisierung von Schlüsselservern in identitätsbasierten Verschlüsselungssystemen - Tezer, Alina

Towards Duality of Multicommodity Multiroute Cuts and Flows: Multilevel Ball-Growing - Kolman, Petr; Scheideler, Christian (Theory of Computing Systems)
An elementary h-route ow, for an integer h 1, is a set of h edge- disjoint paths between a source and a sink, each path carrying a unit of ow, and an h-route ow is a non-negative linear combination of elementary h-routeows. An h-route cut is a set of edges whose removal decreases the maximum h-route ow between a given source-sink pair (or between every source-sink pair in the multicommodity setting) to zero. The main result of this paper is an approximate duality theorem for multicommodity h-route cuts and ows, for h 3: The size of a minimum h-route cut is at least f=h and at most O(log4 k f) where f is the size of the maximum h-routeow and k is the number of commodities. The main step towards the proof of this duality is the design and analysis of a polynomial-time approximation algorithm for the minimum h-route cut problem for h = 3 that has an approximation ratio of O(log4 k). Previously, polylogarithmic approximation was known only for h-route cuts for h 2. A key ingredient of our algorithm is a novel rounding technique that we call multilevel ball-growing. Though the proof of the duality relies on this algorithm, it is not a straightforward corollary of it as in the case of classical multicommodity ows and cuts. Similar results are shown also for the sparsest multiroute cut problem.

Token Dissemination in Geometric Dynamic Networks - Abshoff, Sebastian; Benter, Markus; Cord-Landwehr, Andreas; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics, ALGOSENSORS 2013, Sophia Antipolis, France, September 5-6, 2013, Revised Selected Papers)
We consider the k-token dissemination problem, where k initially arbitrarily distributed tokens have to be disseminated to all nodes in a dynamic network (as introduced by Kuhn et al., STOC 2010). In contrast to general dynamic networks, our dynamic networks are unit disk graphs, i.e., nodes are embedded into the Euclidean plane and two nodes are connected if and only if their distance is at most R. Our worst-case adversary is allowed to move the nodes on the plane, but the maximum velocity v_max of each node is limited and the graph must be connected in each round. For this model, we provide almost tight lower and upper bounds for k-token dissemination if nodes are restricted to send only one token per round. It turns out that the maximum velocity v_max is a meaningful parameter to characterize dynamics in our model.

Three-Valued Abstraction and Heuristic-Guided Refinement for Verifying Concurrent Systems - Timm, Nils
Software systems are playing an increasing role in our everyday life, and as the amount of software applications grows, so does their complexity and the relevance of their computations. Software components can be found in many systems that are charged with safety-critical tasks, such as control systems for aviation or power plants. Hence, software verification techniques that are capable of proving the absence of critical errors are becoming more and more important in the field software engineering. A well-established approach to software verification is model checking. Applying this technique involves an exhaustive exploration of a state space model corresponding to the system under consideration. The major challenge in model checking is the so-called state explosion problem: The state space of a software system grows exponentially with its size. Thus, the straightforward modelling of real-life systems practically impossible. A common approach to this problem is the application of abstraction techniques, which reduce the original state space by mapping it on a significantly smaller abstract one. Abstraction inherently involves a loss of information, and thus, the resulting abstract model may be too imprecise for a definite result in verification. Therefore, abstraction is typically combined with abstraction refinement: An initially very coarse abstract model is iteratively refined, i.e. enriched with new details about the original system, until a level of abstraction is reached that is precise enough for a definite outcome. Abstraction refinement-based model checking is fully automatable and it is considered as one of the most promising approaches to the state explosion problem in verification. However, it is still faced with a number of challenges. There exist several types of abstraction techniques and not every type is equally well-suited for all kinds of systems and verification tasks. Moreover, the selection of adequate refinement steps is nontrivial and typically the most crucial part of the overall approach: Unfavourable refinement decisions can compromise the state space-reducing effect of abstraction, and as a consequence, can easily lead to the failure of verification. It is, however, hard to predict which refinement steps will eventually be expedient for verification – and which not.

Symbiotic Coupling of P2P and Cloud Systems: The Wikipedia Case - Graffi, Kalman; Bremer, Lars (Proceedings of the International Conference on Communications (ICC'13))
Cloud computing offers high availability, dynamic scalability, and elasticity requiring only very little administration. However, this service comes with financial costs. Peer-to-peer systems, in contrast, operate at very low costs but cannot match the quality of service of the cloud. This paper focuses on the case study of Wikipedia and presents an approach to reduce the operational costs of hosting similar websites in the cloud by using a practical peer-to-peer approach. The visitors of the site are joining a Chord overlay, which acts as first cache for article lookups. Simulation results show, that up to 72% of the article lookups in Wikipedia could be answered by other visitors instead of using the cloud.

Service Matching under Consideration of Explicitly Specified Service Variants - Platenius, Marie Christin; von Detten, Markus; Gerth, Christian; Schäfer, Wilhelm; Engels, Gregor (IEEE 20th International Conference on Web Services (ICWS 2013))
One of the main ideas of Service-Oriented Computing (SOC) is the delivery of flexibly composable services provided on world-wide markets. For a successful service discovery,service requests have to be matched with the available service offers. However, in a situation in which no service that completely matches the request can be discovered, the customer may tolerate slight discrepancies between request and offer. Some existing fuzzy matching approaches are able to detectsuch service variants, but they do not allow to explicitly specify which parts of a request are not mandatory. In this paper, we improve an existing service matching approach based onVisual Contracts leveraging our preliminary work of design pattern detection. Thereby, we support explicit specifications of service variants and realize gradual matching results that can be ranked in order to discover the service offer that matches a customer’s request best.

Semi-Automated Software Composition Through Generated Components - Mohr, Felix; Kleine Büning, Hans (Proceedings of the 15th International Conference on Information Integration and Web-based Applications & Services (iiWAS))
Software composition has been studied as a subject of state based planning for decades. Existing composition approaches that are efficient enough to be used in practice are limited to sequential arrangements of software components. This restriction dramatically reduces the number of composition problems that can be solved. However, there are many composition problems that could be solved by existing approaches if they had a possibility to combine components in very simple non-sequential ways. To this end, we present an approach that arranges not only basic components but also composite components. Composite components enhance the structure of the composition by conditional control flows. Through algorithms that are written by experts, composite components are automatically generated before the composition process starts. Therefore, our approach is not a substitute for existing composition algorithms but complements them with a preprocessing step. We verified the validity of our approach through implementation of the presented algorithms.

Seitenkanalresistenz paarungsbasierter Kryptographie - Otte, Oliver

Security Proofs for Pairing-Based Cryptography in the Generic Group Model - Bobolz, Jan

Securing Critical Unattended Systems with Identity Based Cryptography - A Case Study - Blömer, Johannes; Günther, Peter; Krummel, Volker (Proceedings of the 5th International Conference on Mathematical Aspects of Computer and Information Sciences (MACIS))
Unattended systems are key ingredients of various critical infrastruc-tures like networks of self service terminals or automated teller machines.For cost and efficiency reasons they should mostly run autonomously.Unattended systems are attractive and lucrative targets for various kindsof attacks, including attacks on the integrity of their components and thecommunication between components. In this paper, we propose a gen-eral cryptographic framework to protect unattended systems. We alsodemonstrate that instantiating the framework with techniques from iden-tity based cryptography is particularly well-suited to efficiently secureunattended systems.

Routing in heterogenen OpenFlow Netzwerken - Wallaschek, Felix

Ressource-Optimized Deployment of Multi-Tier Applications - The Data Rate-Constrained Case - Robbert, Christoph

Reengineering of Component-Based Software Systems in the Presence of Design Deficiencies - von Detten, Markus
The maintenance of component-based software systems requires up-to-date models of their concrete architecture, i.e. the architecture that is realised in the source code. These models help in systematically planning, analysing and executing typical reengineering activities. Often no or only outdated architectural models of such systems exist. Therefore, various reverse engineering methods have been developed which try to recover a system's components, subsystems and connectors. However, these reverse engineering methods are severely impacted by design deciencies in the system's code base, especially violations of the component encapsulation. As long as design deciencies are not considered in the reverse engineering process, they reduce the quality of the recovered component structures. Despite this impact of design deciencies, no existing architecture reconstruction approach explicitly integrates a systematic deciency detection and removal into the recovery process. Therefore, I have developed Archimetrix. Archimetrix is a tool-supported architecture reconstruction process. It enhances a clustering-based architecture recovery approach with an extensible, pattern-based deciency detection. After the detection of deciencies, Archimetrix supports the software architect in removing the de ciencies and provides the means to preview the architectural consequences of such a removal. I also provide a process to identify and formalise additional deciencies. I validated the approach on three case studies which show that Archimetrix is able to identify relevant deciencies and that the removal of these deciencies leads to an increased quality of the recovered architectures, i.e. they are closer to the corresponding conceptual architectures.

Reducing Nondeterminism in Automated Service Composition - Mohr, Felix; Lettmann, Theodor; Kleine Büning, Hans (Proceedings of the 6th International Conference on Service Oriented Computing and Applications (SOCA))
Automated service composition has been studied as a subject of state based planning for a decade. A great deal of service composition tasks can only be solved if concrete output values of the services are considered in the composition process. However, the fact that those values are not known before runtime leads to nondeterministic planning problems, which have proven to be notoriously difficult in practical automated service composition applications. Even though this problem is frequently recognized, it has still received remarkably few attention and remains unsolved.This paper shows how nondeterminism in automated service composition can be reduced. We introduce context rules as a means to derive semantic knowledge from output values of services. These rules enable us to replace nondeterministic composition operations by less nondeterministic or even completely deterministic ones. We show the validity of our solutions not only theoretically but also have evaluated them practically through implementation.

Reactive Planar Spanner Construction in Wireless Ad Hoc and Sensor Networks - Benter, Markus; Neumann, Florentin; Frey, Hannes (Proceedings of the 32nd IEEE International Conference on Computer Communications (INFOCOM))
Within reactive topology control, a node determines its adjacent edges of a network subgraph without prior knowledge of its neighborhood. The goal is to construct a local view on a topology which provides certain desired properties such as planarity. During algorithm execution, a node, in general, is not allowed to determine all its neighbors of the network graph. There are well-known reactive algorithms for computing planar subgraphs. However, the subgraphs obtained do not have constant Euclidean spanning ratio. This means that routing along these subgraphs may result in potentially long detours. So far, it has been unknown if planar spanners can be constructed reactively. In this work, we show that at least under the unit disk network model, this is indeed possible, by proposing an algorithm for reactive construction of the partial Delaunay triangulation, which recently turned out to be a spanner. Furthermore, we show that our algorithm is message-optimal as a node will only exchange messages with nodes that are also neighbors in the spanner. The algorithm’s presentation is complemented by a rigorous proof of correctness.

Programs from Proofs – A PCC Alternative - Wonisch, Daniel; Schremmer, Alexander; Wehrheim, Heike (Proceedings of the 25th International Conference on Computer Aided Verification (CAV))
Proof-carrying code approaches aim at safe execution of untrusted code by having the code producer attach a safety proof to the code which the code consumer only has to validate. Depending on the type of safety property, proofs can however become quite large and their validation - though faster than their construction - still time consuming. In this paper we introduce a new concept for safe execution of untrusted code. It keeps the idea of putting the time consuming part of proving on the side of the code producer, however, attaches no proofs to code anymore but instead uses the proof to transform the program into an equivalent but more eﬃciently veriﬁable program. Code consumers thus still do proving themselves, however, on a computationally inexpensive level only. Experimental results show that the proof eﬀort can be reduced by several orders of magnitude, both with respect to time and space.

Profitable Scheduling on Multiple Speed-Scalable Processors - Kling, Peter; Pietrzyk, Peter (Proceedings of the 25th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
We present a new online algorithm for profit-oriented scheduling on multiple speed-scalable processors.Moreover, we provide a tight analysis of the algorithm's competitiveness.Our results generalize and improve upon work by \citet{Chan:2010}, which considers a single speed-scalable processor.Using significantly different techniques, we can not only extend their model to multiprocessors but also prove an enhanced and tight competitive ratio for our algorithm.In our scheduling problem, jobs arrive over time and are preemptable.They have different workloads, values, and deadlines.The scheduler may decide not to finish a job but instead to suffer a loss equaling the job's value.However, to process a job's workload until its deadline the scheduler must invest a certain amount of energy.The cost of a schedule is the sum of lost values and invested energy.In order to finish a job the scheduler has to determine which processors to use and set their speeds accordingly.A processor's energy consumption is power $\Power{s}$ integrated over time, where $\Power{s}=s^{α}$ is the power consumption when running at speed $s$.Since we consider the online variant of the problem, the scheduler has no knowledge about future jobs.This problem was introduced by~\citet{Chan:2010} for the case of a single processor.They presented an online algorithm which is $α^{α}+2eα$-competitive.We provide an online algorithm for the case of multiple processors with an improved competitive ratio of $α^{α}$.

Software Engineering for Self-Adaptive Systems: A Second Research Roadmap - de Lemos, Rogrio; Giese, Holger; A. Müller, Hausi; Shaw, Mary; Andersson, Jesper; Litoiu, Marin; Schmerl, Bradley; Tamura, Gabriel; M. Villegas, Norha; Vogel, Thomas; Weyns, Danny; Baresi, Luciano; et al. (Software Engineering for Self-Adaptive Systems II)

Leichtgewichtige Traceability im agilen Entwicklungsprozess am Beispiel von Scrum - Bouillon, Elke; Güldali, Baris; Herrmann, Andrea; Keuler, Thorsten; Moldt, Daniel; Riebisch, Matthias (Softwaretechnik-Trends)

Testen bei Migrationsprojekten - Grieger, Marvin; Güldali, Baris; Sauer, Stefan; Mlynarski, Michael (OBJEKTspektrum (Online Themenspecials))

Maßgeschneidert und werkzeugunterstützt Entwickeln angepasster Requirements Engineering-Methoden - Fazal-Baqaie, Masud; Güldali, Baris; Luckey, Markus; Sauer, Stefan; Spijkerman, Michael (OBJEKTspektrum (Online Themenspecials))

Editorial - Engels, Gregor; Luckey, Markus (Computer Science - Research and Development)

Informationstechnik spart Ressourcen - Engels, Gregor; Gerth, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Müller, Wolfgang; Sauer, Stefan (Forschungsforum Paderborn)

Detection and Resolution of Conflicting Change Operations in Version Management of Process Models - Gerth, Christian; Küster, Jochen; Luckey, Markus; Engels, Gregor (Software and Systems Modeling)

Wirtschaftlichkeitsberechnung für MBT: Wann sich modellbasiertes Testen lohnt - Faragó, David; Törsel, Arne-Michael; Mlynarski, Michael; Weißleder, Stephan; Güldali, Baris; Brandes, Christian (OBJEKTspektrum)
Modellbasiertes Testen verspricht potenziell eine höhere Effizienz und Effektivität im Testprozess. Ob im eigenen Kontext der Einsatz wirtschaftlich ist, ist jedoch häufig unklar. Dieser Beitrag analysiert systematisch Kosten- und Nutzenfaktoren und stellt ein Verfahren zur Abschätzung der Wirtschaftlichkeit des modellbasierten Testens vor. Anhand eines Beispiels wird der Ablauf veranschaulicht.

Object-oriented Modeling of Multimedia Applications - Engels, Gregor; Sauer, Stefan (Handbook of Software Engineering and Knowledge Engineering)

Quality Assurance with Dynamic Meta Modeling - Soltenborn, Christian
Dynamic Meta Modeling (DMM) is a semantics specification technique targeted at MOF-based modeling languages, where a language's behavior is defined by means of graphical operational rules which change runtime models. The DMM approach has first been suggested by Engels et al. in 2000; Hausmann has then defined the DMM language on a conceptual level within his PhD thesis in 2006. Consequently, the next step was to bring the existing DMM concepts alive, and then to apply them to different modeling languages, making use of the lessons learned to improve the DMM concepts as well as the DMM tooling. The result of this process is the DMM++ method, which is presented within this thesis. Our contributions are three-fold: First, and according to our experiences with the DMM language, we have introduced new concepts such as refinement by means of rule overriding, and we have strengthened existing concepts such as the dealing with universally quantified structures or attributes. Second, we have developed a test-driven process for semantics specification: A set of test models is created, and their expected behavior is fixed. Then, the DMM rules are created incrementally, finally resulting in a DMM ruleset realizing at least the expected behavior of the test models. Additionally, we have defined a set of coverage criteria for DMM rulesets which allow to measure the quality of a set of test models. Third, we have shown how functional as well as non-functional requirements can be formulated against models and their DMM specifications. The former is achieved by providing a visual language for formulating temporal logic properties, which are then verified with model checking techniques, and by allowing for visual debugging of models failing a requirement. For the latter, the modeler can add performance information to models and analyze their performance properties, e.g. average throughput.

Business Process Models - Change Management - Gerth, Christian
Driven by the need for a closer alignment of business and IT requirements, the role of business process models in the development of enterprise software systems has increased continuously. Similar to other software artifacts, process models are developed and refined in team environments by several stakeholders, resulting in different versions. These versions need to be merged in order to obtain an integrated process model. Existing solutions to this basic problem in the field of software configuration management are mainly limited to textual documents, e.g., source code. This monograph presents a generally applicable framework for process model change management, which provides easy-to-use comparison and merging capabilities for the integration of different process model versions. The framework supports popular modeling languages such as BPMN, BPEL, or UML Activity Diagrams. Differences between process models are represented in terms of intuitive, high-level change operations. Equipped with a sophisticated analysis of dependencies and a semantic-aware computation of conflicts between differences, the framework constitutes a comprehensive and practically usable solution for process model change management in the model-driven development of enterprise software systems.

How backhaul networks influence the feasibility of coordinated multipoint in cellular networks - Biermann, Thorsten; Scalia, Luca; Choi, Changsoon; Kellerer, Wolfgang; Karl, Holger (IEEE Communications Magazine)

Ein pragmatischer Ansatz zur Entwicklung situationsgerechter Entwicklungsmethoden - Spijkerman, Michael (Software Engineering 2013 - Workshopband (inkl. Doktorandensymposium) SE 2013 (to appear))

Kaos4SOA - Extending KAOS Models with Temporal and Logical Dependencies - Nagel , Benjamin; Gerth , Christian; Post, Jennifer; Engels, Gregor (Proceedings of the CAiSE'13 Forum at the 25th International Conference on Advanced Information Systems Engineering (CAiSE'13))

CVSM 2013 Challenge: Recognizing High-level Edit Operations in Evolving Models. - Kehrer , Timo; Gerth, Christian (Proceedings of the Workshop on Comparison and Versioning of Software Models (CVSM'13))

Wiederverwendbarkeit von Migrationswissen durch Techniken der modellgetriebenen Softwareentwicklung - Grieger , Marvin; Sauer, Stefan (Software Engineering 2013 Workshopband)

Goal-driven Composition of Business Process Models - Nagel , Benjamin; Gerth , Christian; Engels, Gregor (Proceedings of the 9th Workshop on Engineering Service-Oriented Applications (WESOA 2013) (accepted for application))

Assembly-based Method Engineering with Method Patterns - Fazal-Baqaie , Masud; Luckey , Markus; Engels, Gregor (Software Engineering 2013 Workshopband)

Instrumentenentwicklung zur Messung von Lernstrategien in mathematikhaltigen Studiengängen - Göller, Robin; Kortemeyer, Jörg; Liebendörfer, Michael; Biehler, Rolf; Hochmuth, Reinhard; Krämer, Jana; Ostsieker, Laura; Schreiber, Stephan (Beiträge zum Mathematikunterricht 2013: Vorträge auf der 47. Tagung für Didaktik der Mathematik)

Mathe – nein danke? Interesse im und am Mathematikstudium bei Grundschullehramtsstudierenden mit Pflichtfach - Kolter, Jana; Liebendörfer, Michael (Mathematik im Übergang Schule / Hochschule und im ersten Studienjahr)

Interest and Self-Determination in the Transition to Studying Mathematics - Liebendörfer, Michael; Hochmuth, Reinhard (Proceedings of the 37th Conference of the International Group for the Psychology of Mathematics Education)

Interest in Mathematics and the First Steps at the University - Liebendörfer, Michael; Hochmuth, Reinhard (Proceedings of the 8th Conference of European Research in Mathematics Education)

Self-organization of nanospheres in trenches on silicon surfaces - Brassat, Katharina; Assion, Fabian; Hilleringmann, Ulrich; Lindner, Jörg (physica status solidi (a))
The selective deposition and self-assembly of nanospheres from a colloidal suspension in trenches on silicon surfaces is investigated using conventional light, confocal laser scanning and scanning electron microscopy. Trenches with widths of one to several nanosphere diameters are formed on silicon surfaces by photolithography and reactive ion etching. The spreading knife convective self-assembly technique is employed to distribute the nanosphere suspension on the pre-patterned surface. It is shown that this technique is particularly useful in combination with a functionalized surface where a selfassembled molecular monolayer changes the contact angle such that sphere deposition takes place almost exclusively in the trenches. By this, lines selectively filled with a chain of beads with a length of 0.5 mm have been achieved.

Performance and thermal management on self-adaptive hybrid multi-cores - Happe, Markus
Handling run-time dynamics on embedded system-on-chip architectures has become more challenging over the years. On the one hand, the impact of workload and physical dynamics on the system behavior has dramatically increased. On the other hand, embedded architectures have become more complex as they have evolved from single-processor systems over multi-processor systems to hybrid multi-core platforms.Static design-time techniques no longer provide suitable solutions to deal with the run-time dynamics of today's embedded systems. Therefore, system designers have to apply run-time solutions, which have hardly been investigated for hybrid multi-core platforms.In this thesis, we present fundamental work in the new area of run-time management on hybrid multi-core platforms. We propose a novel architecture, a self-adaptive hybrid multi-core system, that combines heterogeneous processors, reconfigurable hardware cores, and monitoring cores on a single chip. Using self-adaptation on thread-level, our hybrid multi-core systems can effectively perform performance and thermal management autonomously at run-time.

On-The-Fly Computing -- Das Entwicklungs- und Betriebsparadigma fürSoftwaresysteme der Zukunft - Engels, Gregor (Proceedings of the Multikonferenz Sofware Engineering 2013 (SE 2013))
Alle Domänen und Branchen der heutigen Wirtschaft sind auf eine effiziente und effektive Entwicklung von benötigten Softwaresystemen angewiesen. Das 40 Jahre alte Prinzip der Beschaffung von Softwaresystemen durch den Einkauf von teuren, relativ unflexiblen Standardlösungen beziehungsweise der noch teureren Erstellung durch Softwarehäuser oder eigene Softwareabteilungen muss deshalb in Frage gestellt werden. Mit dem Einsatz von Cloud Computing-Techniken wird es möglich, Softwaresysteme und die für den Betrieb benötigten Ressourcen nur bei Bedarf und nur in der benötigten Form einzukaufen. Mit dem Ansatz der service-orientierten Architekturen stehen Methoden zur Verfügung, Software zumindest unternehmensintern flexibel zusammenzustellen. Diese ersten Ansätze für eine neue Art der Entwicklung und des Betriebs von Softwaresystemen bilden den Ausgangspunkt für die Forschungen in dem seit 2011 laufenden DFG Sonderforschungsbereich (SFB) 901 „On-The-Fly Computing“ an der Universität Paderborn. Die Vision des On-The-Fly Computing ist, dass die Softwaresysteme der Zukunft aus individuell und automatisch konfigurierten und zur Ausführung gebrachten Softwarebausteinen bestehen, die auf Märkten frei gehandelt werden und flexibel kombinierbar sind. Um zu erforschen, in wie weit diese Vision realisierbar ist, werden Konzepte, Methoden und Techniken entwickelt, die eine weitestgehend automatische Konfiguration, Ausführung und Adaption von Softwaresystemen aus auf weltweiten Märkten verfügbaren Services ermöglichen. Um diese Ziele zu erreichen, arbeiten an der Universität Paderborn Informatiker aus unterschiedlichen Disziplinen wie Softwaretechnik, Algorithmik, Rechnernetze, Systementwurf, Sicherheit und Kryptographie mit Wirtschaftswissenschaftlern zusammen, die ihre spezifische Expertise einbringen, mit der die Organisation und Weiterentwicklung des Marktes vorangetrieben werden kann.

On Two-Party Communication Through Dynamic Networks - Abshoff, Sebastian; Benter, Markus; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Proceedings of the 17th International Conference on Principles of Distributed Systems (OPODIS))
We study two-party communication in the context of directed dynamic networks that are controlled by an adaptive adversary. This adversary is able to change all edges as long as the networks stay strongly-connected in each round. In this work, we establish a relation between counting the total number of nodes in the network and the problem of exchanging tokens between two communication partners which communicate through a dynamic network. We show that the communication problem for a constant fraction of n tokens in a dynamic network with n nodes is at most as hard as counting the number of nodes in a dynamic network with at most 4n+3 nodes. For the proof, we construct a family of directed dynamic networks and apply a lower bound from two-party communication complexity.

On the Quality of Selfish Virtual Topology Reconfiguration in IP-over-WDM Networks - Wette, Philip; Karl, Holger (Proceedings of the 19th IEEE International Workshop on Local and Metropolitan Area Networks (IEEE LANMAN))
The process of planning a virtual topology for a Wavelength Devision Multiplexing (WDM) network is called Virtual Topology Design (VTD). The goal of VTD is to find a virtual topology that supports forwarding the expected traffic without congestion. In networks with fluctuating, high traffic demands, it can happen that no single topology fits all changing traffic demands occurring over a longer time. Thus, during operation, the virtual topology has to be reconfigured. Since modern networks tend to be large, VTD algorithms have to scale well with increasing network size, requiring distributed algorithms. Existing distributed VTD algorithms, however, react too slowly on congestion for the real-time reconfiguration of large networks. We propose Selfish Virtual Topology Reconfiguration (SVTR) as a new algorithm for distributed VTD. It combines reconfiguring the virtual topology and routing through a Software Defined Network (SDN). SVTR is used for online, on-the-fly network reconfiguration. Its integrated routing and WDM reconfiguration keeps connection disruption due to network reconfiguration to a minimum and is able to react very quickly to traffic pattern changes. SVTR works by iteratively adapting the virtual topology to the observed traffic patterns without global traffic information and without future traffic estimations. We evaluated SVTR by simulation and found that it significantly lowers congestion in realistic networks and high load scenarios.

On Greedy Routing in Degree-bounded Graphs over d-Dimensional Internet Coordinate Embeddings - Autenrieth, Marcus; Frey, Hannes (Proceedings of the Conference on Networked Systems (NetSys))
In this paper we will introduce a new d-dimensional graph for constructing geometric application layer overlay net-works. Our approach will use internet coordinates, embedded using the L∞ -metric. After describing the graph structure, we will show how it limits maintenance overhead by bounding each node’s out-degree and how it supports greedy routing using one-hop neighbourhood information in each routing step. We will further show that greedy routing can always compute a path in our graph and we will also prove that in each forwarding step the next hop is closer to the destination than the current node.

MapReduce in Software Defined Networks - Splietker, Malte

Locally Self-Adjusting Tree Networks - Avin, Chen; Häupler, Bernhard; Lotker, Zvi; Scheideler, Christian; Schmid, Stefan (Proceedings of the 27th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
This paper initiates the study of self-adjusting networks (or distributed data structures) whose topologies dynamically adapt to a communication pattern $σ$. We present a fully decentralized self-adjusting solution called SplayNet. A SplayNet is a distributed generalization of the classic splay tree concept. It ensures short paths (which can be found using local-greedy routing) between communication partners while minimizing topological rearrangements. We derive an upper bound for the amortized communication cost of a SplayNet based on empirical entropies of $σ$, and show that SplayNets have several interesting convergence properties. For instance, SplayNets features a provable online optimality under special requests scenarios. We also investigate the optimal static network and prove different lower bounds for the average communication cost based on graph cuts and on the empirical entropy of the communication pattern $σ$. From these lower bounds it follows, e.g., that SplayNets are optimal in scenarios where the requests follow a product distribution as well. Finally, this paper shows that in contrast to the Minimum Linear Arrangement problem which is generally NP-hard, the optimal static tree network can be computed in polynomial time for any guest graph, despite the exponentially large graph family. We complement our formal analysis with a small simulation study on a Facebook graph.

Local and Online Algorithms for Facility Location - Pietrzyk, Peter
Diese Arbeit beschäftigt sich mit dem Facility Location Problem. Dies ist ein Optimierungsproblem, bei dem festgelegt werden muss an welchen Positionen Ressourcen zur Verfügung gestellt werden, so dass diese von Nutzern gut erreicht werden können. Es sollen dabei Kosten minimiert werden, die zum einen durch Bereitstellung von Ressourcen und zum anderen durch Verbindungskosten zwischen Nutzern und Ressourcen entstehen. Die Schwierigkeit des Problems liegt darin, dass man einerseits möglichst wenige Ressourcen zur Verfügung stellen möchte, andererseits dafür sorgen muss, dass sich Nutzer nicht all zu weit weg von Ressourcen befinden. Dies würde nämlich hohe Verbindungskosten nach sich ziehen. Das Facility Location Problem wurde bereits sehr intensiv in vielen unterschiedlichen Varianten untersucht. In dieser Arbeit werden drei Varianten des Problems modelliert und neue Algorithmen für sie entwickelt und bezüglich ihres Approximationsfaktors und ihrer Laufzeit analysiert. Jede dieser drei untersuchten Varianten hat einen besonderen Schwerpunkt. Bei der ersten Varianten handelt es sich um ein Online Problem, da hier die Eingabe nicht von Anfang an bekannt ist, sondern Schritt für Schritt enthüllt wird. Die Schwierigkeit hierbei besteht darin unwiderrufliche Entscheidungen treffen zu müssen ohne dabei die Zukunft zu kennen und trotzdem eine zu jeder Zeit gute Lösung angeben zu können. Der Schwerpunkt der zweiten Variante liegt auf Lokalität, die z.B. in Sensornetzwerken von großer Bedeutung ist. Hier soll eine Lösung verteilt und nur mit Hilfe von lokalen Information berechnet werden. Schließlich beschäftigt sich die dritte Variante mit einer verteilten Berechnung, bei welcher nur eine stark beschränkte Datenmenge verschickt werden darf und dabei trotzdem ein sehr guter Approximationsfaktor erreicht werden muss. Die bei der Analyse der Approximationsfaktoren bzw. der Kompetitivität verwendeten Techniken basieren zum großen Teil auf Abschätzung der primalen Lösung mit Hilfe einer Lösung des zugehörigen dualen Problems. Für die Modellierung von Lokalität wird das weitverbreitete LOCAL Modell verwendet. In diesem Modell werden für die Algorithmen subpolynomielle obere Laufzeitschranken gezeigt.

Knowledge-Based Verification of Service Compositions - An SMT approach - Walther, Sven; Wehrheim, Heike (Proceedings of the 18th IEEE International Conference on Engineering of Complex Computer Systems (ICECCS))
In the Semantic (Web) Services area, services are considered black boxes with a semantic description of their interfaces as to allow for precise service selection and conﬁguration. The semantic description is usually grounded on domain-speciﬁc concepts as modeled in ontologies. This accounts for types used in service signatures, but also predicates occurring in preconditions and effects of services. Ontologies, in particular those enhanced with rules, capture the knowledge of domain experts on properties of and relations between domain concepts. In this paper, we present a veriﬁcation technique for service compositions which makes use of this domain knowledge. We consider a service composition to be an assembly of services of which we just know signatures, preconditions, and effects. We aim at proving that a composition satisﬁes a (user-deﬁned) requirement, speciﬁed in terms of guaranteed preconditions and required postconditions. As an underlying veriﬁcation engine we use an SMT solver. To take advantage of the domain knowledge (and often, to enable veriﬁcation at all), the knowledge is fed into the solver in the form of sorts, uninterpreted functions and in particular assertions as to enhance the solver’s reasoning capabilities. Thereby, we allow for deductions within a domain previously unknown to the solver. We exemplify our technique on a case study from the area of water network optimization software.

IRIS: A Robust Information System Against Insider DoS-Attacks - Eikel, Martina; Scheideler, Christian (Proceedings of the 25th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In this work we present the first scalable distributed information system,i.e., a system with low storage overhead, that is provably robust againstDenial-of-Service (DoS) attacks by a current insider. We allow acurrent insider to have complete knowledge about the information systemand to have the power to block any ε-fraction of its serversby a DoS-attack, where ε can be chosen up to a constant. The taskof the system is to serve any collection of lookup requests with at most oneper non-blocked server in an efficient way despite this attack. Previously,scalable solutions were only known for DoS-attacks of past insiders, where apast insider only has complete knowledge about some past time pointt_0 of the information system. Scheideler et al. (DISC 2007, SPAA 2009) showedthat in this case it is possible to design an information system so that anyinformation that was inserted or last updated after t_0 is safe against a DoS-attack. But their constructions would not work at all for a current insider. The key idea behindour IRIS system is to make extensive use of coding. More precisely, we presenttwo alternative distributed coding strategies with an at most logarithmicstorage overhead that can handle up to a constant fraction of blocked servers.

Incorporating feedback from application layer into routing and wavelength assignment algorithms - Wette, Philip; Karl, Holger (Proceedings of the 32nd IEEE International Conference on Computer Communications (INFOCOM))
Preemptive Routing and Wavelength Assignment (RWA) algorithms preempt established lightpaths in case not enough resources are available to set up a new lightpath in a Wavelength Division Multiplexing (WDM) network. The selection of lightpaths to be preempted relies on internal decisions of the RWA algorithm. Thus, if dedicated properties of the network topology are required by the applications running on the network, these requirements have to be known to the RWA algorithm.Otherwise it might happen that by preempting a particular lightpath these requirements are violated. If, however, these requirements include parametersknown only at the nodes running the application, the RWA algorithm cannot evaluate the requirements. For this reason an RWA algorithm is needed which incorporates feedback from the application layer in the preemption decisions.This work proposes a simple interface along with an algorithm for computing and selecting preemption candidates in case a lightpath cannot be established. We reason about the necessity of using information from the application layer in the RWA and present two example applications which benefit from this idea.

Identifikation und Wiederherstellung von kryptographischen Schlüsseln mit FPGAs - Riebler, Heinrich
Keywords: coldboot

HSkip+: A Self-Stabilizing Overlay Network for Nodes with Heterogeneous Bandwidths - Feldotto, Matthias

Hierarchies in Local Distributed Decision - Meyer auf der Heide, Friedhelm; Swirkot, Kamil
We study the complexity theory for the local distributed setting introduced by Korman, Peleg and Fraigniaud. They have defined three complexity classes LD (Local Decision), NLD (Nondeterministic Local Decision) and NLD^#n. The class LD consists of all languages which can be decided with a constant number of communication rounds. The class NLD consists of all languages which can be verified by a nondeterministic algorithm with a constant number of communication rounds. In order to define the nondeterministic classes, they have transferred the notation of nondeterminism into the distributed setting by the use of certificates and verifiers. The class NLD^#n consists of all languages which can be verified by a nondeterministic algorithm where each node has access to an oracle for the number of nodes. They have shown the hierarchy LD subset NLD subset NLD^#n. Our main contributions are strict hierarchies within the classes defined by Korman, Peleg and Fraigniaud. We define additional complexity classes: the class LD(t) consists of all languages which can be decided with at most t communication rounds. The class NLD-O(f) consists of all languages which can be verified by a local verifier such that the size of the certificates that are needed to verify the language are bounded by a function from O(f). Our main results are refined strict hierarchies within these nondeterministic classes.